2008
DOI: 10.1007/s10543-007-0158-4
|View full text |Cite
|
Sign up to set email alerts
|

On the stability of functionally fitted Runge–Kutta methods

Abstract: Classical collocation RK methods are polynomially fitted in the sense that they integrate an ODE problem exactly if its solution is an algebraic polynomial up to some degree. Functionally fitted RK (FRK) methods are collocation techniques that generalize this principle to solve an ODE problem exactly if its solution is a linear combination of a chosen set of arbitrary basis functions. Given for example a periodic or oscillatory ODE problem with a known frequency, it might be advantageous to tune a trigonometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…However, we established in [12,10] that the coefficients of an FRK method that uses a separable basis are timeindependent (in the sense that they only depend on the current stepsize).…”
Section: Separable Basis Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we established in [12,10] that the coefficients of an FRK method that uses a separable basis are timeindependent (in the sense that they only depend on the current stepsize).…”
Section: Separable Basis Functionsmentioning
confidence: 99%
“…This includes the most common functions, namely monomials, exponentials, trigonometric functions and others. With t 0 = 0 for simplicity, we set [10] for further details on the time-independence of the coefficients. We also draw the attention of the reader to the fact that, similarly to [15,Corollary 1], if we expand the coefficients into Taylor series…”
Section: Definition 33 (Separable Basis) a Set Of Linearly Independmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods are developed to integrate an ODE exactly if the solution of the ODE is a linear combination of some certain basis functions (see, e.g., [2], [7], [8], [12], [13], [14], [17]). For example, trigonometric methods have been developed to solve periodic or nearly periodic problems (see, e.g., [7], [11], [17]).…”
Section: Introductionmentioning
confidence: 99%
“…For example, trigonometric methods have been developed to solve periodic or nearly periodic problems (see, e.g., [7], [11], [17]). Numerical experiments have shown that trigonometrically-fitted methods are superior to classical Runge-Kutta methods for solving ODEs whose solutions are periodic or nearly periodic functions with known frequencies (see, e.g., [8], [11], [12], [13], [14], [16], [17]). …”
Section: Introductionmentioning
confidence: 99%